Thermal resistances model for a soil-to-air thermoelectric generator device. (November 2022) - Ga, Latai; Huang, Shenghui; Zhang, Yuqi; Xu, Daochun; Li, Wenbin
Abstract: Wireless sensor networks (WSNs) are being used more and more often as a result of the Internet of Things' quick growth. The largest constraint on the lifespan of WSNs is the issue with power supply. The thermal resistance model of thermoelectric devices and the thermoelectric conversion model are developed in this paper to solve this problem. The impact of environment on the thermal resistance of the system is examined based on this model, and the voltage and power that the system can produce in various conditions is determined using the thermoelectric conversion model. The system can generate a maximum voltage of 0.52 V and power of 2.24 mW, according to field trial results, which offers a workable solution to the energy constraint issue faced by wireless sensor nodes.